2012
DOI: 10.1002/pon.3088
|View full text |Cite
|
Sign up to set email alerts
|

Depression and cancer survivorship: importance of coping self‐efficacy in post‐treatment survivors

Abstract: Purpose An estimated 30% of cancer patients are expected to experience clinically significant psychological distress during the treatment phase of their disease. Despite significant attention being directed to the mental health needs of individuals undergoing and completing treatment, there is less known about the mental health needs of survivors and the role of potential protective factors in survivorship, such as coping self-efficacy and social support. Method One hundred and twenty-four post-treatment can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
77
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 72 publications
14
77
0
3
Order By: Relevance
“…In addition, the second greatest amount of variance (37 %) was explained in emotional well-being. This finding is consistent with other studies where intrinsic religiousness (Caplan et al, 2013; Fehring et al, 1997; Nelson et al, 2009), religious coping (Gall et al, 2009; Sherman et al, 2009), and self-efficacy for coping with cancer (Albrecht et al, 2013; Merluzzi et al, 2001; Philip et al, 2013) predicted mental health among cancer patients. Overall, it is noteworthy that the model predicted significant variance in all four types of well-being.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the second greatest amount of variance (37 %) was explained in emotional well-being. This finding is consistent with other studies where intrinsic religiousness (Caplan et al, 2013; Fehring et al, 1997; Nelson et al, 2009), religious coping (Gall et al, 2009; Sherman et al, 2009), and self-efficacy for coping with cancer (Albrecht et al, 2013; Merluzzi et al, 2001; Philip et al, 2013) predicted mental health among cancer patients. Overall, it is noteworthy that the model predicted significant variance in all four types of well-being.…”
Section: Discussionsupporting
confidence: 92%
“…Self-efficacy for coping with cancer represents patients’ confidence in their ability to use various strategies to manage major tasks during the course of their illness (Merluzzi et al., 2001). Self-efficacy for coping with cancer has been associated with positive health outcomes such as less fatigue, lower levels of depressive symptoms, and higher quality of life among cancer patients (Albrecht et al., 2013; Merluzzi et al, 2001; Philip et al, 2013). Howsepian and Merluzzi (2009) found that religious beliefs were unrelated to self-efficacy for coping with cancer and psychosocial adjustment to cancer in a predominantly Christian sample of cancer outpatients.…”
mentioning
confidence: 99%
“…As seen in previous research (e.g., (Barbera, et al, 2010; Philip, Merluzzi, Zhang, & Heitzmann, 2012)), women reported a higher concern burden than men, and younger survivors reported more physical, emotional, and employment concerns (Bloom, Petersen, & Kang, 2007; Brant et al, 2011; Foster, Wright, Hill, Hopkinson, & Roffe, 2009; Mao et al, 2007; Meyerowitz, Kurita, & D'Orazio, 2008; Shi, et al, 2011; Smith, Crespi, Petersen, Zimmerman, & Ganz, 2010; B. J. Zebrack, Yi, Petersen, & Ganz, 2008).…”
Section: Discussionsupporting
confidence: 76%
“…5054 Our conclusion that patients with extreme-negative coping behaviors do not progress to UER is therefore predictable. Potentially more surprising, is our finding that, in strict progression-to-UER terms, high coping is not advantageous.…”
Section: Discussionmentioning
confidence: 82%